Teenagers' perceptions of blindness related to smoking: a novel message to a vulnerable group. Issue 5 (6th February 2007) - Moradi, Phillip; Thornton, Judith; Edwards, Richard; Harrison, Roger A; Washington, Stephen J; Kelly, Simon P
Abstract : Background: Cigarette smoking often starts in teenage years. It is not known whether teenagers are aware of the association of smoking with eye disease and blindness. Aim: To explore the knowledge of the link between smoking, and eye diseases and blindness, and the likely impact of this knowledge among teenagers in UK. Methods: A cross-sectional survey, using a structured interview of teenagers attending four organised social events, was conducted. Awareness and fear of blindness, and of three smoking-related diseases (lung cancer, heart disease and stroke) and a distractor condition (deafness) was investigated. The likelihood of smokers quitting on developing early signs of each condition was determined. Results: A 92% "opt in" response rate was achieved. Out of 260 teenagers (16–18 years), 15%, 27% and 81% believed that smoking caused stroke, heart disease and lung cancer, respectively. Only 5% believed smoking caused blindness. Subjects ranked their fear of each of the five conditions, scoring five for the most feared and one for the least feared. Subjects were significantly (p<0.01) more fearful (mean scores in brackets) of blindness (4.2) than of lung cancer (3.4), heart disease (2.3) and deafness (1.2). More teenagers (p<0.01) said they would stop smoking on developing early signs of blindness compared with early signs of lung or heart disease. Conclusions: Awareness of the risk of blindness from smoking is low among teenagers, but fear of blindness may be more likely to motivate teenagers to stop smoking than fear of lung or heart disease. Teenagers should be made more aware of the ocular risks of cigarette smoking as a novel public health measure.